2013
DOI: 10.1007/978-3-642-36645-1_46
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation into the Practical Application of Residential Energy Certificates

Abstract: The Energy Performance of Buildings Directive (EPBD) 2002/91/EC introduced various obligatory requirements intended to achieve the reduction of use of energy resources in buildings and consequentially the reduction of the impact of energy use in buildings. Article 7 of the directive formally specified the current European requirement for the energy certification of buildings. In order to implement this requirement, a general framework for establishing a methodology of calculation of the total energy performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
1
1
0
Order By: Relevance
“…A statistical survey of the certificates submitted in 2011 concluded that the certification methodology applied in Malta provides a reasonable approximation of the actual pattern of energy use in dwellings. The results obtained from this analysis both matched actual data and fell within the bands indicated by other regions with a similar climate (Abela et al, 2012).…”
Section: Compliance and Certificationsupporting
confidence: 81%
“…A statistical survey of the certificates submitted in 2011 concluded that the certification methodology applied in Malta provides a reasonable approximation of the actual pattern of energy use in dwellings. The results obtained from this analysis both matched actual data and fell within the bands indicated by other regions with a similar climate (Abela et al, 2012).…”
Section: Compliance and Certificationsupporting
confidence: 81%
“…The application of energy efficiency procedures makes the public aware of energy saving, as well as environmental and sustainable development [97,98]. The number of innovative companies in the construction industry in Serbia has experienced an increase within the period 2011-2020 [16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%